6x-8-10=2(x-6)

Simple and best practice solution for 6x-8-10=2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-8-10=2(x-6) equation:


Simplifying
6x + -8 + -10 = 2(x + -6)

Reorder the terms:
-8 + -10 + 6x = 2(x + -6)

Combine like terms: -8 + -10 = -18
-18 + 6x = 2(x + -6)

Reorder the terms:
-18 + 6x = 2(-6 + x)
-18 + 6x = (-6 * 2 + x * 2)
-18 + 6x = (-12 + 2x)

Solving
-18 + 6x = -12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-18 + 6x + -2x = -12 + 2x + -2x

Combine like terms: 6x + -2x = 4x
-18 + 4x = -12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-18 + 4x = -12 + 0
-18 + 4x = -12

Add '18' to each side of the equation.
-18 + 18 + 4x = -12 + 18

Combine like terms: -18 + 18 = 0
0 + 4x = -12 + 18
4x = -12 + 18

Combine like terms: -12 + 18 = 6
4x = 6

Divide each side by '4'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| (2z+1)(5-z)=0 | | 10x-92=3x-8 | | 2x+5x=20.34 | | -1/5w-3/2=2w-7/5 | | sin(37)=x/14 | | 2x+9-10=2(x-5)+12 | | (-5x+3)+(-7x-1)= | | -2y-(0)=2y-8 | | 1-3Y=3 | | 6+25x=15x+14 | | A+5=-4a+5 | | -2x+4=-6+26x | | 55-10x=19+8x | | 5m+7n-2(6m-8n)= | | 49/(-7)=-7k/(-7) | | -2(0)+x=2(0)-8 | | 90=-4x | | x=75(x)+7 | | (6-5i)+(7-2i)= | | 42-3x=12+12x | | 441+b*b=841 | | 3b/100 | | 27-4x=12-7x | | y=5/8=-1/4 | | 11x=-35+4 | | 2(x-6)+2x-10= | | .23x=.94 | | 12y=38x-100 | | 8x-(5x-7)= | | k/12=3 | | 5m-6=8 | | 3y/100 |

Equations solver categories